The Key Role of Cold Ionospheric Ions As a Source of Hot Magnetospheric Plasma and As a Driver of the Dynamics of Substorms and Storms - Chappell, C. R.; Glocer, A.; Giles, B. L.; Moore, T. E.; Huddleston, M. M.; Gallagher, D. L. (Frontiers in Astronomy and Space Sciences, 2021)
The solar wind has been seen as the major source of hot magnetospheric plasma since the early 1960's. More recent theoretical and observational studies have shown that the cold (few eV) polar wind and warmer polar cusp plasma that flow continuously upward from the ionosphere can be a very significant source of ions in the magnetosphere and can become accelerated to the energies characteristic of the plasma sheet, ring current, and warm plasma cloak. Previous studies have also shown the presence of solar wind ions in these magnetospheric regions. These studies are based principally on proxy measurements of the ratios of He++/H+ and the high charge states of O+/H+. The resultant admixture of ionospheric and solar wind ions that results has been difficult to quantify, since the dominant H+ ions originating in the ionosphere and solar wind are indistinguishable. The ionospheric ions are already inside the magnetosphere and are filling it from the inside out with direct access from the ionosphere to the center of the magnetotail. The solar wind ions on the other hand must gain access through the outer boundaries of the magnetosphere, filling the magnetosphere from the outside in. These solar wind particles must then diffuse or drift from the flanks of the magnetosphere to the near-midnight reconnection region of the tail which takes more time to reach (hours) than the continuously large outflowing ionospheric polar wind (10's of minutes). In this paper we examine the magnetospheric filling using the trajectories of the different ion sources to unravel the intermixing process rather than trying to interpret only the proxy ratios. We compare the timing of the access of the ionospheric and solar wind sources and we use new merged ionosphere-magnetosphere multi-fluid MHD modeling to separate and compare the ionospheric and solar wind H+ source strengths. The rapid access of the cold polar wind and warm polar cusp ions flowing down-tail in the lobes into the mid-plane of the magnetotail, suggests that , coupled with a southward turning of the IMF Bz, these ions can play a key triggering role in the onset of substorms and larger storms.